Neuropeptide and steroid hormone mediators of neuroendocrine regulation - Heck, A. L.; Crestani, C. C. [UNESP]; Fernández-Guasti, A.; Larco, D. O.; Mayerhofer, A.; Roselli, C. E. (Wiley, 2018)
To maintain the health and well-being of all mammals, numerous aspects of physiology are controlled by neuroendocrine mechanisms. These mechanisms ultimately enable communication between neurones and glands throughout the body and are centrally mediated by neuropeptides and/or steroid hormones. A recent session at the International Workshop in Neuroendocrinology highlighted the essential roles of some of these neuropeptide and steroid hormone mediators in the neuroendocrine regulation of stress-, reproduction- and behaviour-related processes. Accordingly, the present review highlights topics presented in this session, including the role of the neuropeptides corticotrophin-releasing factor and gonadotrophin-releasing hormone in stress and reproductive physiology, respectively. Additionally, it details an important role for gonadal sex steroids in the development of behavioural sex preference.
Keywords: corticotrophin-releasing factor; gonadotrophin-releasing hormone; neuroactive steroids; neuropetides; reproduction; stress